Экспонаты Музея «Пруссия» в Каталоге копий Центрального Римско-Германского музея (Майнц) - Кулаков, Владимир И. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2019)
The catalogue of copies from the Roman-German Central Museum (Mainz) poses an opportunity to present to the modern researcher the volume of Prussian archaeological material available on the second floor dedicated to the 19th century. By collecting what is considered the most representative exhibits, the museum authorities put on display items copied in Mainz and stored in Prussia-Museum (Königsberg). They were created by masters from Aesti and Prussia. The only imports among the small array of findings published in the catalogue include a helmet from the Dollkeim-Kovrovo burial ground (its local origin has not been excluded) and a lock and key from the Löbertshof cemetery / Tyulenino.